2014
DOI: 10.1096/fj.14-251884
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel‐like factor 6 interferes with cellular transformation induced by the H‐ ras oncogene

Abstract: KLF6 is a member of the Krüppel-like factor family of transcription factors, with diverse roles in the regulation of cell physiology, including proliferation, signal transduction, and apoptosis. Mutations or down-regulation of KLF6 have been described in several human cancers. In this work, we found that KLF6-knockdown resulted in the formation of transformed foci and allowed the spontaneous conversion of NIH3T3 cells to a tumorigenic state. We further assessed the role of KLF6 in the context of oncogenic Ras.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 54 publications
(73 reference statements)
4
14
0
Order By: Relevance
“…CCRF-CEM acute lymphoblastic leukemia (ALL) [ 16 ] and K562 chronic myeloid leukemia (CML) [ 17 ] cells and their MDR P-glycoprotein overexpressing variants [ 18 , 19 ], CEM/ADR5000 and Lucena 1, respectively, were a generous gift from Dr. T. Efferth (Institute of Pharmacy and Biochemistry, Johannes Gutenberg University, Mainz, Germany) and Dr. V. Rumjanek (Instituto de Bioquímica Médica Leopoldo de Meis, Universidade Federal do Rio de Janeiro, Rio de Janeiro, Brazil), respectively. The HEK293T non-tumor derived cell line [ 20 ] and human isolated mononuclear cells (PBMC) were also tested. Leukemic and PBMC cells were grown in Roswell Park Memorial Institute (RPMI) 1640 medium (Invitrogen Life Technologies, CA, USA) while the HEK293T cell line was grown in Dulbecco's Modified Eagle's medium (DMEM, Invitrogen Life Technologies, CA, USA), both of these media supplemented with 10% heat-inactivated fetal bovine serum (FBS, PAA Laboratories, Pasching, Austria), 2 mM glutamine (Invitrogen Life Technologies, CA, USA), and penicillin (100 units/mL) streptomycin (100 μ g/mL) (Invitrogen Life Technologies, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CCRF-CEM acute lymphoblastic leukemia (ALL) [ 16 ] and K562 chronic myeloid leukemia (CML) [ 17 ] cells and their MDR P-glycoprotein overexpressing variants [ 18 , 19 ], CEM/ADR5000 and Lucena 1, respectively, were a generous gift from Dr. T. Efferth (Institute of Pharmacy and Biochemistry, Johannes Gutenberg University, Mainz, Germany) and Dr. V. Rumjanek (Instituto de Bioquímica Médica Leopoldo de Meis, Universidade Federal do Rio de Janeiro, Rio de Janeiro, Brazil), respectively. The HEK293T non-tumor derived cell line [ 20 ] and human isolated mononuclear cells (PBMC) were also tested. Leukemic and PBMC cells were grown in Roswell Park Memorial Institute (RPMI) 1640 medium (Invitrogen Life Technologies, CA, USA) while the HEK293T cell line was grown in Dulbecco's Modified Eagle's medium (DMEM, Invitrogen Life Technologies, CA, USA), both of these media supplemented with 10% heat-inactivated fetal bovine serum (FBS, PAA Laboratories, Pasching, Austria), 2 mM glutamine (Invitrogen Life Technologies, CA, USA), and penicillin (100 units/mL) streptomycin (100 μ g/mL) (Invitrogen Life Technologies, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…iRFP-C1 was a gift from Michael Davidson and Vladislav Verkhusha (National Magnetic High Field Laboratory, Tallahassee, FL; Addgene plasmid #54786; ref. 14); shBRCA1 (TRCN0000010305, Sigma-Aldrich) was cloned into pLKO.1-TRC vector through EcoRI and AgeI restriction sites; and shSCR-pLKO.1 was described previously (15). shSCR-plenti (TR30021) and shPLK1-plenti (TL320457 A) were acquired from Origene.…”
Section: Dna Constructs and Shrnamentioning
confidence: 99%
“…KLF6 is reputed as tumor suppressor since numerous reports demonstrate its frequent genomic loss or down-regulation, implying a functional inactivation, in a broad range of human cancers such as glioblastoma, hepatocellular carcinoma, gastric carcinoma, colorectal, prostate, ovarian, breast, and non-small-cell lung cancers (Narla et al, 2001; Kimmelman et al, 2004; Kremer-Tal et al, 2004; Narla et al, 2007; Bureau et al, 2009; DiFeo et al, 2009; Tetreault et al, 2013). In addition, previous reports from our laboratory showed that KLF6 down-regulation leads to spontaneous transformation of NIH3T3 fibroblasts (Trucco et al, 2014). Also, KLF6 ectopic expression impaired H-Ras G12V -mediated cell growth and transformed phenotype (Trucco et al, 2014).…”
Section: Introductionmentioning
confidence: 79%
“…In addition, previous reports from our laboratory showed that KLF6 down-regulation leads to spontaneous transformation of NIH3T3 fibroblasts (Trucco et al, 2014). Also, KLF6 ectopic expression impaired H-Ras G12V -mediated cell growth and transformed phenotype (Trucco et al, 2014).…”
Section: Introductionmentioning
confidence: 79%